CryoEM reveals the stochastic nature of individual ATP binding events in a group II chaperonin - Yanyan Zhao (Nature Portfolio, 2021)
The mechanism by which chaperonins coordinate ATP utilization in their multiple subunits remains unclear. Here, the authors employ an approach that uses cryo-EM single particle analysis to track the number and distribution of nucleotides bound to each subunit in the homo-oligomeric MmCpn archaeal chaperonin complex and observe that ATP binds in a statistically random manner to MmCpn both within a ring and across the rings, which shows that there is no cooperativity in ATP binding to archaeal group II chaperonins under the conditions used in this study.